2015
DOI: 10.3892/etm.2015.2169
|View full text |Cite
|
Sign up to set email alerts
|

Lower esophageal microbiota species are affected by the eradication of Helicobacter pylori infection using antibiotics

Abstract: The aim of this study was to investigate the effect of Helicobacter pylori (H. pylori) infection on the lower esophageal microbiota and the eradication of H. pylori through the use of antibiotics. Forty-five BALB/C mice were randomly divided into negative control, infection and treatment groups. The mice were sacrificed and DNA was extracted from the lower esophageal microbiota. Polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) was performed to determine the composition of the microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…An experimental study from China on H. pylori -infected mice demonstrated that the lower esophageal microbiota was significantly reduced after antibiotic eradication therapy, with further colonization by Staphylococcus, Acinetobacter, and non-spore-forming Bacillus [24]. Alternatively to the acid rebound theory, the authors hypothesized that the observed microecological changes may induce lower esophageal sphincter relaxation and reflux esophagitis following eradication therapy [24]. In addition to these findings, a study from Israel evaluating gastric fluid bacteria in healthy individuals and patients with Gastroesophageal Reflux Disease (GERD) (Barrett 0 s esophagus/reflux esophagitis) confirmed that esophageal and gastric microbial communities were significantly different before and after PPI treatment, mainly showing an increase in families from the phylum Clostridia in the esophagus [25].…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…An experimental study from China on H. pylori -infected mice demonstrated that the lower esophageal microbiota was significantly reduced after antibiotic eradication therapy, with further colonization by Staphylococcus, Acinetobacter, and non-spore-forming Bacillus [24]. Alternatively to the acid rebound theory, the authors hypothesized that the observed microecological changes may induce lower esophageal sphincter relaxation and reflux esophagitis following eradication therapy [24]. In addition to these findings, a study from Israel evaluating gastric fluid bacteria in healthy individuals and patients with Gastroesophageal Reflux Disease (GERD) (Barrett 0 s esophagus/reflux esophagitis) confirmed that esophageal and gastric microbial communities were significantly different before and after PPI treatment, mainly showing an increase in families from the phylum Clostridia in the esophagus [25].…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%
“…The esophageal microbiome has been categorized in two distinct types: type I is seen in normal esophagus and is dominated by the Streptococcus genus, whereas type II is usually seen in esophagitis and Barrett's esophagus and is characterized by a significant decrease in Gram‐positive bacteria and an increase in Gram‐negative anaerobic/microaerophilic bacteria . An experimental study from China on H. pylori ‐infected mice demonstrated that the lower esophageal microbiota was significantly reduced after antibiotic eradication therapy, with further colonization by Staphylococcus, Acinetobacter, and non‐spore‐forming Bacillus . Alternatively to the acid rebound theory, the authors hypothesized that the observed microecological changes may induce lower esophageal sphincter relaxation and reflux esophagitis following eradication therapy .…”
Section: Gastric Microbiota/ H Pylori In Extragastric Diseasesmentioning
confidence: 99%
“…However, H. pylori does not typically colonize the esophagus in high abundance in infected individuals (56). In a mouse model, gastric infection with H. pylori led to an altered esophageal microbiome with increased taxonomic diversity, and H. pylori eradication resulted in a decrease in lower esophageal diversity (57). Thus, H. pylori infection of the stomach in humans may have a direct impact on the lower esophageal microbiome and disease risk.…”
Section: The Role Of H Pylori and The Gastric Microbiomementioning
confidence: 99%
“…Moreover, Helicobacter infection-induced LTi cell-dependent antibacterial peptide production did not elicit significant changes in the gastric microbiome or promote eradication of Candida albicans from the gastric mucosa. Finally, Tian et al investigated microbiota changes in the lower esophagus, by DGGE profile analysis of the 16S rDNA V6 region, following successful eradication of H. pylori-infected mice by administration of antibiotics [55]. This showed an increased number of bacterial species including Acinetobacter, Klebsiella, and Enterobacter species to be present in the lower esophagus of infected mice as com-pared to the control and eradicated groups.…”
Section: Microbiota and H Pylori Infectionmentioning
confidence: 99%
“…Finally, Tian et al. investigated microbiota changes in the lower esophagus, by DGGE profile analysis of the 16S rDNA V6 region, following successful eradication of H. pylori ‐infected mice by administration of antibiotics . This showed an increased number of bacterial species including Acinetobacter, Klebsiella, and Enterobacter species to be present in the lower esophagus of infected mice as compared to the control and eradicated groups.…”
Section: Microbiota and H Pylori Infectionmentioning
confidence: 99%